2021
DOI: 10.1103/physrevb.103.014512
|View full text |Cite
|
Sign up to set email alerts
|

Third harmonic generation from collective modes in disordered superconductors

Abstract: Recent experiments with strong THz fields in both conventional and unconventional superconductors have clearly evidenced a marked third-harmonic generation below the superconducting temperature T c . Its interpretation challenged substantial theoretical work aimed at establishing the relative efficiency of quasiparticle excitations and collective modes in triggering such a resonant response. Here we compute the nonlinear current by implementing a time-dependent Bogoljubov-de Gennes approach, with the twofold a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(98 citation statements)
references
References 49 publications
(358 reference statements)
4
93
0
1
Order By: Relevance
“…Moreover, while the density-related effect is hard to handle in the quasiclassical Eilenberger equation, the vanishing chargedensity fluctuation in the second-order response, which agrees with the charge conservation, is obtained within the GIKE and path-integral approach. Consequently, the present work resolves the controversies among various studies in the literature (whether the experimentally observed third-harmonic current [26][27][28][29][30][31][32] is attributed to the Higgs-mode [29][30][31][32][33]48 or charge-density-fluctuation [49][50][51] generation, and whether one has to rely on impurity to explain the experimentally observed Higgs-mode generation 33,45,[48][49][50][51]54,55,57,58 ), and can therefore help understanding the experimental findings.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Moreover, while the density-related effect is hard to handle in the quasiclassical Eilenberger equation, the vanishing chargedensity fluctuation in the second-order response, which agrees with the charge conservation, is obtained within the GIKE and path-integral approach. Consequently, the present work resolves the controversies among various studies in the literature (whether the experimentally observed third-harmonic current [26][27][28][29][30][31][32] is attributed to the Higgs-mode [29][30][31][32][33]48 or charge-density-fluctuation [49][50][51] generation, and whether one has to rely on impurity to explain the experimentally observed Higgs-mode generation 33,45,[48][49][50][51]54,55,57,58 ), and can therefore help understanding the experimental findings.…”
Section: Discussionmentioning
confidence: 55%
“…However, rather than straightening out the situation, these theoretical descriptions make the understanding of the existing and growing experimental findings muddled. Specifically, early theoretical studies of the nonlinear optical response in superconductors have used the Bloch [26][27][28][29][30][34][35][36][37][38][39][40] or Liouville [41][42][43][44][45] equation derived in Anderson pseudospin picture 46 , with the vector potential A alone. The second-order light-matter interaction H p = e 2 A 2 τ 3 /(2m) naturally emerges in these descriptions [26][27][28][29][30][34][35][36][37][38][39][41][42][43][44] as a pseudo field along z direction, with τ i being the Pauli matrices in Nambu space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…д. ), связанные с нелинейным взаимодействием электромагнитных (ЭМ) волн (см., например, [1][2][3][4]). В то же время недостаточно изучены нелинейные явления в плотных заряженных системах (кулоновских системах и плазме), вызванные квадратичной реакцией на электромагнитное поле -генерация второй гармоники (ГВГ), параметрическая генерация излучения (ПГИ) (см.…”
Section: Introductionunclassified
“…Recently, collective natures of materials are investigated by nonlinear optical spectroscopies. For example, in BCS superconductors, the amplitude (Higgs) mode, which is dark in linear response regime, is activated by the nonlinear optical drive and the resulting resonance emerges in third-harmonic generation (THG) [59][60][61][62][63][64]. Actually, the enhancement of the THG intensity at the resonant frequency has been observed by the terahertz pump-probe experiments [65][66][67][68][69].…”
Section: Introductionmentioning
confidence: 99%